GONGGANG RI SADOQKOQ: MORFOLOGI CERITA RAKYAT VLADIMIR PROPP (Gonggang ri Sadoqkoq: Morphology of Folklore by Vladimir Propp) - Hasina Fajrin R. (SAWERIGADING, 2014)
Gonggang ri Sadoqkoq is one of Torajanese oral tradition that is important to preserve. Applying descriptive method using Vladimir Propp theory that analyzes character function, scheme and pattern of the story, and the way the characters are introcuded uncover the uniqueness and the exclusivity owned by the oral tradition mentioned. Character functions found in Gonggang ri Sadoqkoq are nine functions and three spheres of action. The nine functions involve two willingness pattern, namely having wife that could accompany Gonggang and having descendant in order to make the overwhelming wealth owned by him could be bequathed. Apparently, there is deux ex machine character then have much influence the function in structure. The function is not mentioned in thirty one functions mentioned by Vladimir Propp.